Effect of two different RAFT reactions on grafting MMA from pre-irradiated PP film. (June 2019) - Gao, Yuting; Chen, Yan; Yang, Liming; Rodrigues, Luisa C.; Reis, Rui L.; Chen, Jie
Abstract: The graft polymerization of methyl methacrylate (MMA) from pre-irradiated polypropylene (PP) films mediated by two different addition-fragmentation chain transfer (RAFT) polymerization mechanisms—surface-initiated RAFT polymerization and interface-mediated RAFT polymerization was studied. In the first mechanism, electron beam irradiation technique was applied to produce the initial radical active sites and peroxides on PP films. 4-cyanopentanoic acid dithiobenzoate (CPADB) was added in the solution to mediate the graft polymerization. In the second mechanism, a new technique utilizing the decomposition and recombination of peroxides produced by electron beam and di(thiobenzoyl) disulfide (DBDS) to anchor CTA on PP films was applied. GPC, ATR-FTIR, XPS, SEM and water contact angle were used to characterize graft layer. Surface-initiated RAFT polymerization was found to be fast and facile with high degree of grafting (Dg) and large number-average molecular weight. But the samples after reaction were swelling and out of shape. Interface-mediated RAFT polymerization led to rather low Dg and low molecular weight. But the samples kept their pristine shapes and had better surface properties. Highlights: Two different RAFT polymerizations was applied to graft MMA from PP film. A novel approach to tether CTA on the PP film was raised. The new RAFT model can control the pre-irradiation polymerization. The new RAFT model can form flat and controllable polymer brush.